The Newcastle Control Score: a new method of grading the severity of intermittent distance exotropia. Issue 2 (21st January 2004) - Haggerty, H; Richardson, S; Hrisos, S; Strong, N P; Clarke, M P
Abstract : Aim: To describe the development and application of a novel scoring system for grading the severity of intermittent distance exotropia (IDEX) and its potential application as an intervention criterion for surgical intervention. Methods: The Newcastle Control Score (NCS) for IDEX was developed by incorporating both subjective (home control) and objective (clinic control) criteria into a scale to grade severity. The score structure described was evaluated for interobserver and test-retest reliability. To determine an optimal score threshold for surgical intervention, 170 cases of IDEX were scored retrospectively. Cure rates for surgical and non-surgical cases were then compared according to preoperative or presenting scores. Results: Interobserver and test-test reliability were good ( r = 0.82 and r = 0.89 respectively). Total cure rate with surgery was 54% and without surgery 18% (χ 2 = 23.093, df = 1, p<0.001). Significantly fewer patients with NCS ⩾3 achieved cure without surgery than those with NCS 2 (χ 2 = 3.362, df = 1, p<0.047). Conclusions: The NCS is a reliable method for grading the severity of IDEX and aids decisions regarding intervention. Patients with a score of 3 or more are unlikely to attain a cure without surgery.